Nilai-Nilai Karakter dalam Pembelajaran Tema Diriku Menggunakan Kurikulum 2013 pada Siswa Kelas 1 Sekolah Dasar - M Maryono; Nova Novita (Jurnal Gentala Pendidikan Dasar, 2016)
This study aims to describe what character values ​​are formed in the implementation of my theme learning using 2013 Curriculum on grade 1 students of SDN 131 / IV Jambi City. This type of research is descriptive qualitative with research informants, namely class teacher. To collect data carried out observations, interviews and documentation. Based on the results of the study it can be concluded that the teacher embodies the character values ​​of students through directing students to always pray to the ultimate God so that the knowledge taught is useful and easily obtained by reading prayers, directing students to always maintain class cleanliness, and living in harmony with classmates, motivate students to work on assignments independently, invite students to listen and listen to the material delivered calmly and orderly, give assignments to students, invite students to use objects around the school, provide opportunities for students to show their work in painting, guide students in working training and giving direction to students that work at home should be done at home not at school, providing opportunities for students to ask for material that is not understood, exchanging student seats every day, teachers inviting students to play while learning outside the classroom, directing the student students to help each other, provide motivation to students not to lazy in attending lessons and assign assignments to students.